Design and experiment of cone disk centrifugal shellfish seeding device - Zhang, Hanbing; Li, Pengpeng; Zhang, Haonan; Huang, Wei; Zhang, Guochen; Mu, Gang; Li, Xiuchen (Frontiers in Marine Science, 2023)
This paper designed a centrifugal shellfish seeding device with a conical disc structure to improve the seeding efficiency and uniformity of the centrifugal shellfish seeding device. The dynamic model of the shellfish seedling moving on the conical disk is established, and the main parameters affecting the shellfish seedling's movement characteristics are determined as the cone angle of the impeller, the impeller's speed, and the offset angle of the blade. Using the EDEM software and the shellfish seedling dropping rate as the influencing factors, a single factor simulation test was performed. The research found that the variation trend of shellfish seedling distribution in a single statistical area gradually decreased along the horizontal direction of both sides, with the origin being the center of the seedling sowing device. Test orthogonal rotation simulations using the variation coefficient of seedling distribution uniformity and the effective job width as evaluation indicators. Use Design Expert software to optimize the structure of the seedling sowing device based on the test results, and determine the optimal structure with the maximum width and the minimum variation coefficient as constraints: the impeller cone angle is 7.72 °, and the blade offset angle is -0.9 °. Use the above-mentioned seeding device for simulation and actual seeding testing. The simulation results show that when the impeller speed is 750r/min and the blanking rate is 0.65kg/s, the variation coefficient of seedling distribution uniformity and the effective job width are 12.84% and 24.98m, respectively, while the actual test results are 13.77% and 23.25m, respectively. The object of the seedling performance test was commonly used size shellfish seedlings of the Philippines clam. The results showed that the impeller speed, blanking rate, quadratic term of shellfish seedling size, quadratic term of blanking rate, and interactive term of impeller speed and blanking rate had significant effects on the variation coefficient of the distribution uniformity of shellfish seedlings (P<0.01). Shellfish seedling size, impeller speed, and interactive term of impeller speed and blanking rate all had a significant impact on job width (P<0.01). The results of this study provide a reference for the mechanized design of shellfish seeding.